2011
DOI: 10.1007/s00520-011-1223-8
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of oral mucositis pain by NASA near-infrared light-emitting diodes in bone marrow transplant patients

Abstract: Purpose:To investigate the use of extra-orally applied near infra-red (NIR) phototherapy for the reduction of oral pain secondary to chemo-and radiation-therapy induced mucositis in adult and pediatric hematopoietic stem cell transplant (HSCT) patients. Methods: 80 HSCT were divided into regular (R) and low (L) risk groups, then to experimental (E) and placebo (P) groups, resulting in 4 groups (ER, EL, PR, PL). Experimental subjects received (670 (+/-10) nm galliumaluminum-arsinide light emitting diode (LED) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 38 publications
1
34
0
3
Order By: Relevance
“…All studies except one were published as full text articles [38]. One study reported outcomes as a stratified analysis by underlying disease diagnosis and HSCT regimen [19] and thus, represented two separate analyses for a total of 19 prophylactic LLLT comparisons randomizing 1144 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies except one were published as full text articles [38]. One study reported outcomes as a stratified analysis by underlying disease diagnosis and HSCT regimen [19] and thus, represented two separate analyses for a total of 19 prophylactic LLLT comparisons randomizing 1144 patients.…”
Section: Resultsmentioning
confidence: 99%
“…One study was a solely pediatric trial [41]. Intraoral laser therapy was used in all except two trials [19]. With respect to laser source, InGaAlP (6 trials) and helium-neon (5 trials) were the most commonly used lasers.…”
Section: Resultsmentioning
confidence: 99%
“…It indicated that LLLT significantly reduces pain, severity, and duration of symptoms in patients with OM [44]. Additional data from a trial with near-infrared light-emitting diodes applied extraorally in children and adults with hematological malignancies and solid tumors treated with HSCT demonstrated that the technology can significantly reduce patient-reported pain [45]. A recent randomized study in patients with malignancies treated with HSCT confirmed that oral mucositis incidence and severity can be reduced with LLLT [46].…”
Section: Discussionmentioning
confidence: 98%
“…Whereas in most studies, PBM is applied intra-orally on the oral mucosal tissues, studies indicate that it may also be administered extra-orally, with a resultant effect on structures at risk for OM transcutaneously, thereby enhancing the ease of delivery and possibly the efficacy of treatment [23, 26]. …”
Section: The Potential Utility Of Pbm In the Management Of Side-effecmentioning
confidence: 99%